Mechanisms of pyruvate kinase M2 isoform inhibits cell motility in hepatocellular carcinoma cells - Chen, Yan-Ling (World J Gastroenterol, 2015)
AIM: To investigate biological mechanisms underlying pyruvate kinase M2 isoform (PKM2) regulation of cell migration and invasion in hepatocellular carcinoma cells. METHODS: HepG2 and Huh-7 hepatocellular carcinoma cell lines were stably transfected and cultured in DMEM (HyClone, Logan, UT, United States). To investigate the effects of PKM2 on cellular proliferation, hepatocellular carcinoma cells were subjected to the Cell Counting Kit-8 (Dojindo, Kamimashiki-gun, Kumamoto, Japan). And investigate the effects of PKM2 on cell signal pathway related with migration and invasion, Western immunoblotting were used to find out the differential proteins. All the antibody used was purchaseed from Cell Signal Technology. In order to explore cell motility used Transwell invasion and wound healing assays. The transwell plate with 0.5 mg/mL collagen type I (BD Bioscience, San Jose, CA)-coated filters. The wound-healing assay was performed in 6-well plates. Total RNA was extracted using TRIzol reagent (Invitrogen, CA, United States) and then reverse transcription was conducted. Quantitative reverse transcription-polymerase chain reaction (PCR) analysis was performed with the ABI 7500 real-time PCR system (Applied Biosystems). We further use digital gene expression tag profiling and identification of differentially expressed genes. RESULTS: The cells seeded in four 96-well plates were measured OD450 by conducted Cell Counting Kit-8. From this conduction we observed that both HepG2 and Huh-7 hepatocellular carcinoma cells with silenced PKM2 turn on a proliferate inhibition; however, cell migration and invasion were enhanced compared with the control upon stimulation with epidermal growth factor (EGF). Our results indicate that the knockdown of PKM2 decreased the expression of E-cadherin and enhanced the activity of the EGF/EGFR signaling pathway, furthermore up-regulate the subsequent signal molecular the PLCγ1 and extracellular signal-regulated kinase 1/2 expression in the hepatocellular carcinoma cell lines HepG2 and Huh-7, which regulates cell motility. These variations we observed were due to the activation of the transforming growth factor beta (TGFβ) signaling pathway after PKM2 knockdown. We also found that the expression of TGFBRI was increased and the phosphorylation of Smad2 was enhanced. Taken together, our findings demonstrate that PKM2 can regulate cell motility through the EGF/EGFR and TGFβ/TGFR signaling pathways in hepatocellular carcinoma cells. CONCLUSION: PKM2 play different roles in modulating the proliferation and metastasis of hepatocellular carcinoma cells, and this finding could help to guide the future targeted therapies.